A Susceptible Period of Photic Day-Night Rhythm Loss in Common Marmoset Social Behavior Development - Koshiba, Mamiko; Watarai-Senoo, Aya; Karino, Genta; Ozawa, Shimpei; Kamei, Yoshimasa; Honda, Yoshiko; Tanaka, Ikuko; Kodama, Tohru; Usui, Setsuo; Tokuno, Hironobu (Frontiers in Behavioral Neuroscience, 2021)
There is a rapidly increasing worldwide prevalence of neurodevelopmental psychiatric disorders such as pervasive developmental disorders. These developmental disorders are known to be influenced by an individual’s genetic background but potential biological responses to early life’s environmental exposure to both physical and psychological factors must also be considered. The rich human environment, getting shorter night rest might occur simultaneously, and various kinds of influence in pathogenesis of the developmental disorders are considerations reported in many studies. We previously examined how a longer day-time impacted the psychosocial development of common marmoset (Callithrix jacchus) reared under constant daylight from birth and then reared individually by human nursing under constant light (LL) in juvenile development. Their behaviors were compared with those of normal day-night cycle (LD) marmosets and reared one under constant dark (DD) by multivariate analysis based on principal component analysis (PCA). LL marmosets relatively elicited alert calls and side-to-side shakes of the upper body with rapid head rotation through adulthood frequently. Based on the PCA, these behaviors were interpreted as ‘alert’ or ‘hyperactive’ states. However, the report did not clarify susceptible periods of the photic rhythm loss experience and the psychological development output. Thus, this report is to summarize the following studies in our model animal colonies, 30 animals (11 female, 19 males) for the purpose to further explore critical age states with questions about each social behavior profiling. We compared social behaviors of three age stages, juvenile, adolescent and young adult equivalent to one another in four LL experience conditions, LL (postnatal day (P) 0-150), Early (P60-149, Late (P150-239) and LD (no experience). In the most representative 1st and 2nd principal component scores, the shifting to higher frequency of alert behaviors developed at the adult stage in LL, Early, then Late in turn. The no LL experience group, LD, generally featured higher frequency of local preference of high position comparing to LL experience present groups, in adulthood. This limited model study might inspire different developmental age sensitive mechanisms of neuronal network controlling socio-emotional functions by utilizing the multivariate visualization method, BOUQUET, potentially to contribute neuropharmacological designs for social developmental disorders.